Macroeconomic Variables, International Islamic Indices, and The Return Volatility in Jakarta Islamic Index - Pratama, Yoghi Citra; Azzis, Abdul (UNIVERSITAS ISLAM NEGERI SYARIF HIDAYATULLAH JAKARTA, 2018)
According to understand the behavior of Islamic equity markets the primary objective of this research is to analyze the effect of macroeconomic indicators and International Islamic Index on return volatility of Jakarta Islamic Index. The analysis method used in this study is AutoRegressive Conditional Heteroscedastic-Generalized AutoRegressive Conditional Heteroscedastic (ARCH-GARCH). The result of this research showed that all variables, i.e., BI rate, inflation rate, IDR-USD exchange rate, DJIUS index, DJIUK index, FTSJP index and FTSMY index have a simultaneously significant impact on return volatility of JII. While t-test results show that BI rate, IDR-USD exchange rate, DJIUK index and FTSMY index have a substantial effect on return volatility of JII.DOI: 10.15408/aiq.v10i1.5550